The Influence of Islamic Branding and Life Style on Decisions to Purchase Muslimah Fashion Products in Makassar City With Celebrity Endorsement as a Moderating Variable - Hadisa, Nur; Haddade, Abd. Wahid; Parmitasari, Rika Dwi Ayu (Universitas Muhammadiyah Makassar, 2024)
This research aims to examine the factors that influence consumers in making product purchasing decisionsfashion Muslim women in Makassar City through influenceislamic branding to the Purchase Decision,life that muchon Purchase Decisions, moderation effectCelebrity endorsement betweenislamic branding on purchasing decisions and moderating effectsCelebrity endorsement betweenlife style to the purchase decision. The type of research used is quantitative. The approach used in this research is causal associative. The method in this research is through collecting primary data by distributing questionnaires and secondary data through reference journals related to the research topic. The sampling technique uses the Heir formula with a sample size of 225. The data analysis technique used in this research isSPSS 26. The results of this research show thatIslamic branding dan life style has a positive and significant effect on product purchasing decisionsfashion Muslim women in Makassar City and for moderation,celebrity endorsement does not moderate the relationship betweenIslamic branding on purchasing decisions is different fromLife style in this case,celebrity endorsement strengthen the relationship betweenlife style to the purchase decision. The implications of this research show that consumers should filter all information and interactions, both on the internet and in the surrounding environment, and continue to base Islamic teachings in their daily lives because a person's lifestyle is formed from the results of interactions with their environment. Consumers also have to choose which celebrities can direct us to goodness and adhere to Islamic values. For the perpetratorsindustry fashion Muslim women in particular can show that the materials and manufacturing processfashion Muslim women are in accordance with Islamic values so that consumers are increasingly confident in purchasing products. Then, future researchers can examine other variables that are not yet in this research related to purchasing decisions.